Always look back: eye movements as a reflection of anaphoric encapsulation in Spanish while reading the neuter pronoun ello - Parodi, Giovanni; Julio, Cristóbal; Nadal, Laura; Burdiles, Gina; Cruz, Adriana (Journal of pragmatics, 2018)
Eye movements constitute an important cue to understanding how readers connect textual information, particularly when an encapsulator pronoun must be anaphorically resolved in order to construct a coherent mental representation of the text being read. While existing research into anaphoric reference has predominantly focused on the distance between pronouns and referents and on their morphosyntactic features, no previously published studies have addressed the effect in causal contexts of varying extensions of the referent being encapsulated by a neuter pronoun. In the present research, we help fill this gap by studying the effects of online processing of the anaphoric neuter Spanish pronoun ello (‘this’ in English) in causally-related texts using two varying referent extensions: short and long antecedent. A one factor repeated measures design was implemented. The results of three eye reading measures showed a fine-grained picture of encapsulation processes for seventy-two Chilean university students as they each read twelve texts. On the one hand, the reading times for processing the neuter pronoun ello AOI did not show statistically significant differences between the short and long conditions. On the other, the findings indicate that, in constructing referential and relational coherence in causally-related texts in Spanish, resolution of the neuter pronoun is in fact influenced by the extension of the referent.
Gesehen am 21.02.2020